2000
DOI: 10.4049/jimmunol.165.6.3492
|View full text |Cite
|
Sign up to set email alerts
|

Mage-3 and Influenza-Matrix Peptide-Specific Cytotoxic T Cells Are Inducible in Terminal Stage HLA-A2.1+ Melanoma Patients by Mature Monocyte-Derived Dendritic Cells

Abstract: Dendritic cell (DC) vaccination, albeit still in an early stage, is a promising strategy to induce immunity to cancer. We explored whether DC can expand Ag-specific CD8+ T cells even in far-advanced stage IV melanoma patients. We found that three to five biweekly vaccinations of mature, monocyte-derived DC (three vaccinations of 6 × 106 s.c. followed by two i.v. ones of 6 and 12 × 106, respectively) pulsed with Mage-3A2.1 tumor and influenza matrix A2.1-positive control peptides as well as the recall Ag tetanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
96
1
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(105 citation statements)
references
References 21 publications
(28 reference statements)
6
96
1
2
Order By: Relevance
“…murine and human dendritic cells, and Kalínski et al (46) found that IL-4 secreted by Th2 cells mediates high level IL-12 p70 production by immature human dendritic cells. We confirm these data and extend them in that we show the effect of IL-4 in an FCS-free culture system relevant for adoptive immunotherapy and for populations of mature monocyte-derived dendritic cells, i.e., those dendritic cells that are able to prime naive T cells and are preferentially used in immunotherapy (50,51).…”
Section: Augmenting Effects Of Il-4: Relevancesupporting
confidence: 69%
“…murine and human dendritic cells, and Kalínski et al (46) found that IL-4 secreted by Th2 cells mediates high level IL-12 p70 production by immature human dendritic cells. We confirm these data and extend them in that we show the effect of IL-4 in an FCS-free culture system relevant for adoptive immunotherapy and for populations of mature monocyte-derived dendritic cells, i.e., those dendritic cells that are able to prime naive T cells and are preferentially used in immunotherapy (50,51).…”
Section: Augmenting Effects Of Il-4: Relevancesupporting
confidence: 69%
“…With increased understanding of the requirements for initiating immunity, dendritic cells (DCs) 3 have become attractive vectors for immunotherapy of this and other cancers (2)(3)(4)(5)(6)(7)(8)(9). DCs are proving to be effective in initiating and expanding immune responses in humans (10,11), providing a rationale for their use as adjuvants for active immunization against melanoma (12)(13)(14)(15)(16). Different strategies have been developed to load DCs with tumor Ags, including MHC-restricted synthetic peptides derived from the Ag (12)(13)(14)(15)(16)(17), tumor RNA (18,19), tumor lysates (20), tumor-derived exosomes (21), and dying tumor cells (22)(23)(24)(25)(26); these have been assessed in preclinical models and, in some cases, clinical trials (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)…”
mentioning
confidence: 99%
“…DCs are proving to be effective in initiating and expanding immune responses in humans (10,11), providing a rationale for their use as adjuvants for active immunization against melanoma (12)(13)(14)(15)(16). Different strategies have been developed to load DCs with tumor Ags, including MHC-restricted synthetic peptides derived from the Ag (12)(13)(14)(15)(16)(17), tumor RNA (18,19), tumor lysates (20), tumor-derived exosomes (21), and dying tumor cells (22)(23)(24)(25)(26); these have been assessed in preclinical models and, in some cases, clinical trials (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Tumor cells (dying cells or Ab-coated tumor cells) are of interest as an antigenic source, because the DCs would have the potential to present a broad range of tumor-associated Ags and on both MHC class I and II products regardless of the MHC haplotype of the patient (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Because of the demonstrable host immune response to melanoma and the current understanding of tumor immunology, vaccine therapy is being investigated as a therapeutic strategy for melanoma (7)(8)(9)(10)(11)(12)(13). Dendritic cells (DCs) 3 are the most potent APCs, highly specialized to prime T cell-dependent Ag-specific immune responses (14 -17).…”
mentioning
confidence: 99%